Alignment of poultry sector actors with avian influenza control in Kenya - Onkundi, Dennis; Bett, Bernard; Omore, Amos; Randolph, Thomas (International Food Policy Research Institute, 2010)
Kenya has a high risk of being infected with highly pathogenic avian influenza (HPAI) because it (i) lies along the migratory bird routes, (ii) engages in formal and informal cross-border trade in live birds and other poultry products, (iii) lacks capacity to regulate the poultry industry trade and (iv) is well connected to the region and with the rest of the world through its air and road transport networks. The government developed a contingency plan for prevention and control of the disease in 2005 which describes a set of mitigation measures that could be implemented at various stages of the outbreak. The contingency plan identifies national and international agencies as well poultry value chain actors as being key players that would either deliver or implement HPAI control measures. It has not been established, however, whether these players would comply appropriately to ensure the successful implementation of the HPAI control measures. This is because actor willingness to comply depends fundamentally on the alignment of control measures with actor capacity to comply, their current practices, and incentives they face. This study (i) characterised control measures in terms of expected degree of compliance by actors in the poultry value chain and the agents responsible for implementing the measures, and (ii) identified actors who may be expected to prove to be compliance fail-points to successful implementation of control measures. Four HPAI control measures were studied: these are biosecurity, reporting, movement control, and culling and compensation.